PENGARUH TERPAAN MEDIA SOSIAL PADA AKUN TIKTOK @exploremajalengka TERHADAP MINAT BERKUNJUNG KE TEMPAT WISATA DI MAJALENGKA - Ghozali, Ahmad Ghozali (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
@exploremajalengka is a TikTok account to reach users and encourage them to visit Majalengka tourist attractions. The purpose of this study is to find out how much influence social media exposure has on the @exploremajalengka account on the interest in visiting Majalengka tourism. This study uses the uses and gratification theory and uses a quantitative explanatory research method with non-probability sampling method using a purposive sampling technique of 100 respondents following the TikTok account @exploremajalengka. The results of this study indicate that exposure to the social media TikTok @exploremajalengka has a significant effect on interest in visiting Majalengka tourist attractions. Other findings reveal that the influence value of TikTok's social media exposure is quite high with a value of 59.3% and the rest is influenced by other variables that are not in this study.